Method for preparing 3, 4-dihydropyran through catalysis of meso-porous silicon-based heteropolyacid group

By using mesoporous silicon-based heteropolyacid catalysts, 3,4-dihydropyran is efficiently catalyzed under low temperature conditions, and the problems of high reaction temperature and easy catalyst deactivation in the existing process are solved, achieving high efficiency, Catalytic effect of low energy consumption.

CN119490471APending Publication Date: 2025-02-21DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311045237.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing process of dehydrating tetrahydrofurfuryl alcohol to produce 3,4-dihydropyran has problems such as excessive reaction temperature and easy deactivation of γ-alumina catalyst, resulting in high energy consumption and poor catalyst stability.

Method used

The mesoporous silicon-based heteropolyacid catalyst is used to achieve a catalytic effect of maintaining high activity and long life under low temperature conditions through specific preparation methods and reaction conditions, and avoiding carbon deposits and inactivation.

Benefits of technology

It effectively reduces the reaction temperature, improves the stability and service life of the catalyst, significantly reduces energy and material consumption, and improves the conversion and selectivity of 3,4-dihydropyran.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004402166120000051
    Figure BDA0004402166120000051
  • Figure BDA0004402166120000052
    Figure BDA0004402166120000052
  • Figure BDA0004402166120000053
    Figure BDA0004402166120000053
Patent Text Reader

Abstract

The invention relates to a method for preparing 3, 4-dihydropyran. According to the method, tetrahydrofurfuryl alcohol is adopted as a reactant, and under the catalytic action of a mesoporous silicon-based heteropolyacid catalyst, 3, 4-dihydropyran is prepared through a reaction. The reaction conditions are as follows: the reaction is carried out in a fixed bed reactor at normal pressure, the reaction temperature is 150-240 DEG C, and the feeding mass space velocity of tetrahydrofurfuryl alcohol is 0.1-2.0 h <-1 >. The method is characterized in that meso-porous silicon-based heteropolyacid is used as a catalyst, the catalyst is simple to prepare, has relatively good stability and can efficiently catalyze tetrahydrofurfuryl alcohol to selectively generate 3, 4-dihydropyran, and the conversion rate of the catalyst is gt; the selectivity of the 3, 4-dihydropyran is gt; 95%. The method is characterized in that the reaction temperature is greatly reduced, product carbonization caused by acidity of the catalyst under a high-temperature condition is effectively reduced, the catalyst has good stability, the service life of the catalyst is remarkably prolonged, and the catalytic efficiency of the catalyst is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing 3,4-dihydropyran, and in particular to a method for preparing 3,4-dihydropyran by dehydrating tetrahydrofurfuryl alcohol using a mesoporous silicon-based heteropolyacid-based catalyst. Background Art

[0002] As the only renewable carbon resource in nature, biomass can be used to produce liquid fuels, platform chemicals, high value-added chemicals, etc. through the biorefining process. Furfural is one of the largest biomass-based platform chemicals today, with a global available production capacity of more than 600kt / a, and has the potential to become a major substitute for fossil resources. Furfural is hydrogenated in the gas phase to produce tetrahydrofurfuryl alcohol (THFA), which can be dehydrated in the gas phase to produce 3,4-dihydropyran (DHP). DHP is a six-membered oxygen-containing heterocyclic compound that can be used as a pharmaceutical intermediate and alcohol group protection reagent; it is widely used as a hydroxyl group protection reagent; DHP has active chemical properties and can be used to produce tetrahydropyran, pentanediol, glutaric acid, valerolactone, pentadiene and resin products through polymerization, hydrogenation, oxidation and other reactions. The preparation of DHP by dehydration of tetrahydrofurfuryl alcohol has important industrial significance in the fields of organic chemistry and polymer materials.

[0003] The existing DHP synthesis process mainly uses γ-alumina as a catalyst to make tetrahydrofurfuryl alcohol undergo ring expansion and dehydration at high temperature (usually above 280 degrees) to obtain it. However, both tetrahydrofurfuryl alcohol and DHP are very active chemicals, and are very easy to carbonize under high temperature and strong acidic conditions, resulting in the active center of the γ-alumina catalyst being covered with carbon deposits, and the activity gradually decreases, so that the yield of DHP is only high in the initial stage (patent example); the catalyst needs to be repeatedly regenerated, resulting in high energy consumption of the entire process. Yamada et al. [Applied Catalysis A: General, 2013, 453, 213-218] studied the catalytic performance of Cu-modified alumina in the THFA dehydration reaction and found that when hydrogen flow is added, the catalytic stability and DHP selectivity can be improved, but the selectivity of DHP is still no more than 90%, and other hydrogenation by-products are generated.

[0004] In view of the problems of high reaction temperature and easy deactivation of γ-alumina catalyst in the existing tetrahydrofurfuryl alcohol dehydration process for preparing DHP, it is imperative to develop a new catalytic system and catalytic reaction process for the conversion of tetrahydrofurfuryl alcohol to prepare 3,4-dihydropyran, improve the conversion efficiency and catalyst stability, and further reduce the energy consumption and material consumption of the process of dehydration of tetrahydrofurfuryl alcohol to prepare 3,4-dihydropyran. Summary of the invention

[0005] The purpose of the present invention is to provide a catalytic system for preparing DHP by dehydrating tetrahydrofurfuryl alcohol. The catalyst prepared by the method can maintain high activity and long life under low temperature conditions, and effectively reduce carbon deposition and deactivation in the reaction process.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] The raw material is tetrahydrofurfuryl alcohol, the catalyst is a mesoporous silicon-based heteropolyacid catalyst, the product is 3,4-dihydropyran, and the reaction temperature is 150°C-250°C, preferably 180°C-240°C.

[0008] The preparation method of the mesoporous silicon-based heteropoly acid catalyst is as follows: under the condition of 20-50°C, according to a certain ratio of ingredients, concentrated HCl (35-36%), ethyl silicate, heteropoly acid or heteropoly acid salt are added to the aqueous solution of the template agent, and after stirring for a period of time (2-48 hours), the obtained colloid is transferred to a hydrothermal kettle, crystallized at 50-200°C for 12-72 hours, vacuum filtered, washed, vacuum dried at 100°C for 8-24 hours, and finally calcined at 200-600°C for 2-12 hours to remove the template agent, thereby obtaining a mesoporous silicon-based heteropoly acid catalytic material.

[0009] The preparation process of the mesoporous silicon-based heteropoly acid catalyst is as follows: according to a certain ratio of ingredients, sodium hydroxide aqueous solution and silica sol are added to the aqueous solution of the template agent in sequence, and the mixture is vigorously stirred and mixed evenly, and then the heteropoly acid is added to obtain an amorphous gel, which is transferred to a hydrothermal reactor and sealed, and crystallized at 120°C for 5 days; after the crystallization is completed, it is cooled to room temperature with water, the crystallized product is separated by centrifugation and fully washed with water until it is neutral, and then dried at 100°C for 12 hours, and then calcined at 300°C for 3 hours, 400°C for 3 hours, and 500°C for 7 hours to obtain a mesoporous silicon-based heteropoly acid catalytic material.

[0010] The active group heteropoly acid of the mesoporous silicon-based heteropoly acid catalyst can be one or more of phosphotungstic acid, phosphomolybdic acid, silicotungstic acid, silicomolybdic acid and phosphomolybdic acid.

[0011] The mass content of the heteropoly acid in the mesoporous silicon-based heteropoly acid catalyst is 2%-60%, preferably 5%-30%.

[0012] The mesoporous silica specifically includes one or a mixture of two or more of SBA-15 and SBA-3 in the SBA series and MCM-41, MCM-48 and MCM-50 molecular sieves in the M41S series.

[0013] The template agent specifically includes one or a mixture of two or more of cetyltrimethylammonium bromide (CTAB), polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), cetylpyridinium bromide, polyvinyl alcohol, nonylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, and imidazole long alkyl chain ionic liquid.

[0014] The imidazolyl long alkyl chain ionic liquid includes [C 14 mim][Br]、[C 16 mim][Br],

[0015] [C 18 mim][Br] or a mixture of two or more thereof.

[0016] The device is a fixed bed reactor, and the reaction is carried out at normal pressure.

[0017] After the mesoporous silicon-based heteropolyacid-based catalyst is filled in the reaction tube, the reaction is placed in a fixed bed reactor for reaction.

[0018] The mass space velocity of tetrahydrofurfuryl alcohol feed is 0.1-3.0h -1 , the catalyst bed thickness is 10mm-50mm.

[0019] The method is characterized in that: the mesoporous silicon-based heteropoly acid is used as a catalyst, the catalyst preparation is simple, the catalyst has good stability, and the catalyst can efficiently catalyze tetrahydrofurfuryl alcohol to selectively generate 3,4-dihydropyran, the conversion rate is >99%, and the selectivity of 3,4-dihydropyran is >95%. The method is characterized in that: the reaction temperature is greatly reduced, the acidity of the catalyst is effectively reduced to cause carbonization of the product under high temperature conditions, the catalyst has good stability, and the service life and catalytic efficiency of the catalyst are significantly improved.

[0020] The beneficial effects of the present invention are:

[0021] (1) Mesoporous silicon-based heteropolyacid catalysts have both the high activity of heteropolyacid molecules and the pores of mesoporous materials. They can efficiently catalyze the dehydration of tetrahydrofurfuryl alcohol to 3,4-dihydropyran at relatively low reaction temperatures, effectively avoiding high-temperature carbonization of the reaction raw materials and products. At the same time, the pores of the mesoporous materials can also effectively inhibit the formation of carbon deposits, thereby further improving their stability.

[0022] (2) During the preparation of the mesoporous silica-based heteropolyacid catalyst, heteropolyacid molecules are introduced and embedded in the pore walls of the mesoporous material to form a whole with the pore walls, thereby forming a strong mesoporous silica-based heteropolyacid material and avoiding the loss of the active components of the heteropolyacid. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents.

[0024] All raw materials of the present invention are not particularly limited in purity, and the reagents used in the following examples are all commercially available. Qualitative analysis of the reaction product: Agilent gas chromatography-mass spectrometry is used to qualitatively analyze the reaction product 1,5-pentanediol, which is confirmed by mass spectrometry library retrieval combined with standard substance retention time comparison. Quantitative analysis of the reaction product: Agilent gas chromatography-mass spectrometry is used to qualitatively analyze the reaction products 3,4-dihydropyran, tetrahydropyran, and 2-hydroxytetrahydropyran, which are confirmed by mass spectrometry library retrieval combined with standard substance retention time comparison. Quantitative analysis of the reaction product: Agilent gas chromatograph (chromatographic column is FFAP capillary column, FID hydrogen ion flame detector) is used to quantitatively analyze the product by internal standard method, and the internal standard is N, N-dimethylformamide. Drawing of internal standard working curve: accurately weigh 4.0g of N,N-dimethylformamide, the standard substance of tetrahydrofurfuryl alcohol, 3,4-dihydropyran, tetrahydropyran, and 2-hydroxytetrahydropyran, to prepare the standard solution mother solution, then take 0.2g, 0.4g, 0.6g, 0.8g, and 1.0g from the mother solution respectively, dissolve 0.25N,N-dimethylformamide, add 1.5mL acetonitrile to make up the volume, and then perform gas phase analysis to record the analytes (tetrahydrofurfuryl alcohol, 3,4-dihydropyran, tetrahydropyran, and 2-hydroxytetrahydropyran) respectively. The peak area ratio of tetrahydrofurfuryl alcohol, 3,4-dihydropyran, tetrahydropyran, 2-hydroxytetrahydropyran) and standard N,N-dimethylformamide (Ai / As, where Ai represents the chromatographic peak area of ​​the analyte and As represents the chromatographic peak area of ​​the standard) is taken as the horizontal coordinate, and the mass ratio mi / ms of tetrahydrofurfuryl alcohol, 3,4-dihydropyran, tetrahydropyran, 2-hydroxytetrahydropyran and N,N-dimethylformamide in each solution is calculated as the vertical coordinate, and the standard working curve of the raw material and the product is drawn to calculate the yield of the product. In the following examples, the conversion rate of tetrahydrofurfuryl alcohol and the selectivity of 3,4-dihydropyran, tetrahydropyran and 2-hydroxytetrahydropyran are defined by the following formula:

[0025]

[0026]

[0027]

[0028]

[0029] 3,4-dihydropyran yield (%) = 3,4-dihydropyran selectivity * tetrahydrofurfuryl alcohol conversion rate * 100

[0030] Tetrahydropyran yield (%) = Tetrahydropyran selectivity * Tetrahydrofurfuryl alcohol conversion rate * 100

[0031] 2-Hydroxytetrahydropyran selectivity (%) = 2-Hydroxytetrahydropyran selectivity * tetrahydrofurfuryl alcohol conversion rate * 100

[0032] Example 1: 6.0 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) was dissolved in 180 ml of water, and then 36 wt% of HCI was added to the aqueous solution of P123 to adjust the pH to 1.5, and stirred at 40°C until dissolved, and then 15.0 g of tetraethyl orthosilicate (TEOS) was added, and then 30% of the mass fraction of phosphotungstic acid in the final catalyst product was added, and stirred at 40°C for 24 hours, and the mixed solution was transferred to a hydrothermal autoclave, crystallized at 100°C for 24 hours, vacuum filtered and washed, and then vacuum dried at 100°C for 24 hours, and finally calcined at 450°C for 5 hours. SBA-15-based phosphotungstic acid-30 catalyst-1# with a loading of 30 wt% was obtained.

[0033] Example 2: Change in the amount of active ingredient

[0034] Take 6.0g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) and dissolve it in 180 ml of water, then add 36wt% of HCI to the aqueous solution of P123 to adjust the pH to 1.5, stir at 40°C until dissolved, then add 15.0g of tetraethyl orthosilicate (TEOS), then add 2% of phosphotungstic acid by mass in the final catalyst product, stir at 40°C for 24 hours, transfer the mixed solution to a hydrothermal autoclave, crystallize at 100°C for 24h, vacuum filter and wash, vacuum dry at 100°C for 24h, and finally calcine at 450°C for 5h. Obtain SBA-15-based phosphotungstic acid-2 catalyst-2# with a loading of 2wt%.

[0035] Example 3: Change in the amount of active ingredient

[0036] Take 6.0g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) and dissolve it in 180 ml of water, then add 36wt% HCI to the aqueous solution of P123 to adjust the pH to 1.5, stir at 40°C until dissolved, then add 15.0g of tetraethyl orthosilicate (TEOS), then add 10% of phosphotungstic acid by mass in the final catalyst product, stir at 40°C for 24 hours, transfer the mixed solution to a hydrothermal autoclave, crystallize at 100°C for 24h, vacuum filter and wash, vacuum dry at 100°C for 24h, and finally calcine at 450°C for 5h. Obtain SBA-15-based phosphotungstic acid-10 catalyst-3# with a loading of 10wt%.

[0037] Example 4: Change in the amount of active ingredient

[0038] Take 6.0g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) and dissolve it in 180 ml of water, then add 36wt% HCl to the aqueous solution of P123 to adjust the pH to 1.5, stir at 40°C until dissolved, then add 15.0g of tetraethyl orthosilicate (TEOS), then add 40% of phosphotungstic acid by mass in the final catalyst product, stir at 40°C for 24 hours, transfer the mixed solution to a hydrothermal autoclave, crystallize at 100°C for 24h, vacuum filter and wash, vacuum dry at 100°C for 24h, and finally calcine at 450°C for 5h. Obtain SBA-15-based phosphotungstic acid-40 catalyst-4# with a loading of 40wt%.

[0039] Example 5: Change in the amount of active ingredient

[0040] Take 6.0g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) and dissolve it in 180 ml of water, then add 36wt% HCl to the aqueous solution of P123 to adjust the pH to 1.5, stir at 40°C until dissolved, then add 15.0g of tetraethyl orthosilicate (TEOS), then add 60% of the mass fraction of phosphotungstic acid in the final catalyst product, stir at 40°C for 24 hours, transfer the mixed solution to a hydrothermal kettle, crystallize at 100°C for 24h, vacuum filter and wash, vacuum dry at 100°C for 24h, and finally calcine at 450°C for 5h. Obtain SBA-15-based phosphotungstic acid-60 catalyst-5# with a loading of 60wt%.

[0041] Example 6: Heteropolyacid Types

[0042] Take 6.0g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) and dissolve it in 180 ml of water, then add 36wt% HCl to the aqueous solution of P123 to adjust the pH to 1.5, stir at 40°C until dissolved, then add 15.0g of tetraethyl orthosilicate (TEOS), then add 30% of the mass fraction of phosphomolybdic acid in the final catalyst product, stir at 40°C for 24 hours, transfer the mixed solution to a hydrothermal autoclave, crystallize at 100°C for 24h, vacuum filter and wash, vacuum dry at 100°C for 24h, and finally calcine at 450°C for 5h. Obtain SBA-15-based phosphomolybdic acid-30 catalyst-6# with a loading of 30wt%.

[0043] Example 7: Heteropolyacid Types

[0044] Take 6.0g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) and dissolve it in 180 ml of water, then add 36wt% HCl to the aqueous solution of P123 to adjust the pH to 1.5, stir at 40°C until dissolved, then add 15.0g of tetraethyl orthosilicate (TEOS), then add 30% of silicotungstic acid by mass in the final catalyst product, stir at 40°C for 24 hours, transfer the mixed solution to a hydrothermal autoclave, crystallize at 100°C for 24h, vacuum filter and wash, vacuum dry at 100°C for 24h, and finally calcine at 450°C for 5h. Obtain SBA-15-based silicotungstic acid-30 catalyst-7# with a loading of 30wt%.

[0045] Example 8: Heteropolyacid Types

[0046] Take 6.0g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) and dissolve it in 180ml of water, then add 36wt% HCl to the aqueous solution of P123 to adjust the pH to 1.5, stir at 40℃ until dissolved, then add 15.0g of tetraethyl orthosilicate (TEOS), then add 30% of phosphomolybdic acid by mass in the final catalyst product, stir at 40℃ for 24 hours, transfer the mixed solution to a hydrothermal kettle, crystallize at 100℃ for 24h, vacuum filter and wash, vacuum dry at 100℃ for 24h, and finally calcine at 450℃ for 5h. Obtain SBA-15-based phosphomolybdic acid-30 catalyst-8# with a loading of 30wt%.

[0047] Example 9: Mesoporous Silica Types

[0048] Take 1.5 grams of hexadecyltrimethylammonium bromide (CTAB) and dissolve it in 120 milliliters of distilled water, then add sodium hydroxide aqueous solution and silica sol in order according to the stoichiometric ratio, the molar ratio composition is 2NaO:10SiO2:2CTAB:400H2O, stir vigorously and mix evenly, then add 30% of the mass fraction of phosphotungstic acid in the final catalyst product to obtain an amorphous gel, then transfer it to a hydrothermal reactor and seal it, crystallize it at 120°C for 5 days; after the crystallization is completed, cool it to room temperature with water, centrifuge and separate the crystallized product and wash it with water until it is neutral, then dry it at 100°C for 12 hours, then roast it at 300°C for 3 hours, 400°C for 3 hours, and 500°C for 7 hours. Obtain MCM-41-based phosphotungstic acid-30 catalyst-9# with a loading of 30wt%.

[0049] Example 10: Template Type

[0050] Take 1.5 grams of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) and dissolve it in 120 milliliters of distilled water, then add sodium hydroxide aqueous solution and silica sol in order according to the stoichiometric ratio, the molar ratio composition is 2NaO:10SiO2:2P123:400H2O, stir vigorously and mix evenly, then add 30% of the mass fraction of phosphotungstic acid in the final catalyst product to obtain an amorphous gel, then transfer it to a hydrothermal reactor and seal it, crystallize it at 120°C for 5 days; after the crystallization is completed, cool it to room temperature with water, centrifuge and separate the crystallized product and wash it with water until it is neutral, then dry it at 100°C for 12 hours, then roast it at 300°C for 3 hours, 400°C for 3 hours, and 500°C for 7 hours. Obtain MCM-41-based phosphotungstic acid-30 catalyst-10# with a loading of 30wt%.

[0051] Example 11: Template Type

[0052] Take 1.5g of cetylpyridine bromide and dissolve it in 120mL of distilled water, then add sodium hydroxide aqueous solution and silica sol in order according to the stoichiometric ratio, the molar ratio composition is 2NaO:10SiO2:2 cetylpyridine bromide:400H2O, stir vigorously to mix evenly, then add 30% of the mass fraction of phosphotungstic acid in the final catalyst product to obtain an amorphous gel, then transfer it to a hydrothermal reactor and seal it, crystallize it at 120°C for 5 days; after the crystallization is completed, cool it to room temperature with water, centrifuge and separate the crystallized product and wash it with water until it is neutral, then dry it at 100°C for 12 hours, then roast it at 300°C for 3 hours, 400°C for 3 hours, and 500°C for 7 hours. Obtain MCM-41-based phosphotungstic acid-30 catalyst-11# with a loading of 30wt%.

[0053] Example 12: Template Type

[0054] Take 1.5g polyvinyl alcohol and dissolve it in 120ml distilled water, then add sodium hydroxide aqueous solution and silica sol in order according to the stoichiometric ratio, the molar ratio composition is 2NaO:10SiO2:2 polyvinyl alcohol:400H2O, stir vigorously and mix evenly, then add 30% of the mass fraction of phosphotungstic acid in the final catalyst product to obtain an amorphous gel, then transfer it to a hydrothermal reactor and seal it, crystallize it at 120℃ for 5 days; after the crystallization is completed, cool it to room temperature with water, centrifuge and separate the crystallized product and wash it with water until it is neutral, then dry it at 100℃ for 12 hours, then roast it at 300℃ for 3 hours, 400℃ for 3 hours, and 500℃ for 7 hours. Obtain MCM-41-based phosphotungstic acid-30 catalyst-12# with a loading of 30wt%.

[0055] Example 13: Template Type

[0056] Take 1.5 grams of nonylphenol polyoxyethylene ether and dissolve it in 120 milliliters of distilled water, then add sodium hydroxide aqueous solution and silica sol in order according to the stoichiometric ratio, the molar ratio composition is 2NaO:10SiO2:2 nonylphenol polyoxyethylene ether:400H2O, stir vigorously and mix evenly, then add 30% of the mass fraction of phosphotungstic acid in the final catalyst product to obtain an amorphous gel, then transfer it to a hydrothermal reactor and seal it, crystallize it at 120°C for 5 days; after the crystallization is completed, cool it to room temperature with water, centrifuge and separate the crystallized product and wash it with water until it is neutral, then dry it at 100°C for 12 hours, then roast it at 300°C for 3 hours, 400°C for 3 hours, and 500°C for 7 hours. Obtain MCM-41-based phosphotungstic acid-30 catalyst-13# with a loading of 30wt%.

[0057] Example 14: Template Type

[0058] Take 1.5g of fatty alcohol polyoxyethylene ether and dissolve it in 120ml of distilled water, then add sodium hydroxide aqueous solution and silica sol in order according to the stoichiometric ratio, the molar ratio composition is 2NaO:10SiO2:2 fatty alcohol polyoxyethylene ether:400H2O, stir vigorously and mix evenly, then add 30% of the mass fraction of phosphotungstic acid in the final catalyst product to obtain an amorphous gel, then transfer it to a hydrothermal reactor and seal it, crystallize it at 120℃ for 5 days; after the crystallization is completed, cool it to room temperature with water, centrifuge and separate the crystallized product and wash it with water until it is neutral, then dry it at 100℃ for 12 hours, then roast it at 300℃ for 3 hours, 400℃ for 3 hours, and 500℃ for 7 hours. Obtain MCM-41-based phosphotungstic acid-30 catalyst-14# with a loading of 30wt%.

[0059] Example 15: Template Type

[0060] Take hexadecyl imidazole bromide ([C 16mim][Br])1.5 was dissolved in 120 ml of distilled water, and then sodium hydroxide aqueous solution and silica sol were added in sequence according to the stoichiometric ratio, with a molar ratio of 2NaO:10SiO2:2

[0061] [C 16 mim][Br]:400H2O, stir vigorously to mix evenly, then add 30% of the mass fraction of phosphotungstic acid in the final catalyst product to obtain an amorphous gel, then transfer to a hydrothermal reactor and seal it, crystallize it at 120°C for 5 days; after the crystallization, cool it to room temperature with water, centrifuge and separate the crystallized product, wash it with water until it is neutral, then dry it at 100°C for 12 hours, then calcine it at 300°C for 3 hours, 400°C for 3 hours, and 500°C for 7 hours. Obtain MCM-41-based phosphotungstic acid-30 catalyst-15# with a loading of 30wt%.

[0062] Comparative Example 1 (without heteropolyacid): 6.0 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) was dissolved in 180 ml of water, and then 36 wt% of HCl was added to the aqueous solution of P123 to adjust the pH to 1.5, and stirred at 40°C until dissolved, and then 15.0 g of tetraethyl orthosilicate (TEOS) was added, and stirred at 40°C for 24 hours, and the mixed solution was transferred to a hydrothermal kettle, crystallized at 100°C for 24 hours, vacuum filtered and washed, and then vacuum dried at 100°C for 24 hours, and finally calcined at 450°C for 5 hours. SBA-15 catalyst-16# was obtained.

[0063] Comparative Example 2 (impregnation method): 6.0 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) was dissolved in 180 ml of water, and then 36 wt% of HCl was added to the aqueous solution of P123 to adjust the pH to 1.5, and stirred at 40°C until dissolved, and then 15.0 g of tetraethyl orthosilicate (TEOS) was added, and stirred at 40°C for 24 hours, and the mixed solution was transferred to a hydrothermal kettle, crystallized at 100°C for 24 hours, vacuum filtered and washed, and then vacuum dried at 100°C for 24 hours, and finally calcined at 450°C for 5 hours. SBA-15 carrier was obtained. Then, phosphotungstic acid was loaded on the surface of SBA-15 by an equal volume impregnation method to obtain SBA-15-based phosphotungstic acid-30 supported catalyst-17# with a loading of 30 wt%.

[0064] Comparative Example 3:

[0065] Take hexadecyltrimethylammonium bromide (CTAB) and dissolve it in distilled water, then add sodium hydroxide aqueous solution and silica sol in order according to the stoichiometric ratio, the molar ratio composition is 2NaO:10SiO2:2CTAB:400H2O, stir vigorously and mix evenly to obtain an amorphous gel, then transfer to a hydrothermal reactor and seal it, crystallize it at 120°C for 5 days; after the crystallization is completed, cool it to room temperature with water, centrifuge and separate the crystallized product, wash it with water until it is neutral, then dry it at 100°C for 12 hours, then roast it at 300°C for 3 hours, 400°C for 3 hours, and 500°C for 7 hours. MCM-41 catalyst-18# is obtained.

[0066] Comparative Example 4:

[0067] Take hexadecyltrimethylammonium bromide (CTAB) and dissolve it in distilled water, then add sodium hydroxide aqueous solution and silica sol in order according to the stoichiometric ratio, the molar ratio composition is 2NaO:10SiO2:2CTAB:400H2O, stir and mix vigorously to obtain an amorphous gel, then transfer to a hydrothermal reactor and seal it, crystallize it at 120℃ for 5 days; after the crystallization, cool it to room temperature with water, centrifuge and separate the crystallized product, wash it with water until it is neutral, then dry it at 100℃ for 12 hours, then calcine it at 300℃ for 3 hours, 400℃ for 3 hours, and 500℃ for 7 hours. Obtain MCM-41 carrier with a loading of 30wt%, then use equal volume impregnation method to load phosphotungstic acid on the surface of SBA-15 to obtain MCM-41-based phosphotungstic acid-30 supported catalyst-19# with a loading of 30wt%.

[0068] Embodiment 16-30

[0069] The catalyst prepared as above was applied to the reaction of catalyzing the dehydration of tetrahydrofurfuryl alcohol to 3,4-dihydropyran. The catalysts were pressed into tablets, and the catalysts with a mesh size of 20-40 were sieved and filled into a fixed bed reaction tube with an inner diameter of 6 mm and a length of 300 mm. The thickness of the catalyst bed was 20 mm. Before the reaction, the catalyst was pretreated in flowing nitrogen at 600°C for 1 h. After the pretreatment, the catalyst bed was cooled to a reaction temperature of 220°C, and the mass space velocity of tetrahydrofurfuryl alcohol was 0.5 h -1 , under normal pressure. Samples were taken every 2 hours for gas chromatography analysis. The effects of the content and type of the active components of the catalyst on its catalytic activity for the dehydration of tetrahydrofurfuryl alcohol to 3,4-dihydropyran are shown in Table 1.

[0070]

[0071]

[0072] The effects of different types of mesoporous silica and template agents on their catalytic activity for dehydration of tetrahydrofurfuryl alcohol to 3,4-dihydropyran are shown in Table 2:

[0073]

[0074]

[0075] Example 31-35 Reaction Temperature

[0076] SBA-15-based phosphotungstic acid-30 catalyst-1# was used to catalyze the dehydration of tetrahydrofurfuryl alcohol to produce 3,4-dihydropyran. The catalysts were pressed into tablets, and the catalysts with a mesh size of 20-40 were screened and filled into a fixed bed reaction tube with an inner diameter of 6mm and a length of 300mm. The thickness of the catalyst bed was 20mm. Before the reaction, the catalyst was pretreated in flowing nitrogen at 600°C for 1h. After the pretreatment, the catalyst bed was cooled to a reaction temperature of 150-240°C, and the mass space velocity of tetrahydrofurfuryl alcohol was 0.5h -1 , under normal pressure. Samples were taken every 2 hours for gas chromatography analysis. The tetrahydrocanol conversion rate and the selectivity of 3,4-dihydropyran are shown in Table 3.

[0077]

[0078] Comparative Example 5

[0079] SBA-15 catalyst-16# was used to catalyze the dehydration of tetrahydrofurfuryl alcohol to produce 3,4-dihydropyran. The catalysts were pressed into tablets, and the catalysts with a mesh size of 20-40 were screened and filled into a fixed bed reaction tube with an inner diameter of 6mm and a length of 300mm. The thickness of the catalyst bed was 20mm. Before the reaction, the catalyst was pretreated in flowing nitrogen at 600°C for 1h. After the pretreatment, the catalyst bed was cooled to a reaction temperature of 200°C, and the mass space velocity of tetrahydrofurfuryl alcohol was 0.5h -1 , under normal pressure. Samples were taken every 2 hours for gas chromatography analysis. After 24 hours of continuous operation, the conversion rate of tetrahydrocarbyl alcohol decreased from the initial 30% to 5%, and the selectivity of 3,4-dihydropyran increased from 90% to the final 80%.

[0080] Comparative Example 6

[0081] SBA-15-based phosphotungstic acid-30 supported catalyst-17# was used to catalyze the dehydration of tetrahydrofurfuryl alcohol to 3,4-dihydropyran. The catalysts were pressed into tablets, and the catalysts with a mesh size of 20-40 were sieved and filled into a fixed bed reaction tube with an inner diameter of 6mm and a length of 300mm. The thickness of the catalyst bed was 20mm. Before the reaction, the catalyst was pretreated in flowing nitrogen at 600°C for 1h. After the pretreatment, the catalyst bed was cooled to a reaction temperature of 200°C, and the mass space velocity of tetrahydrofurfuryl alcohol was 0.5h-1 , under normal pressure. Samples were taken every 2 hours for gas chromatography analysis. After 48 hours of continuous operation, the conversion rate of tetrahydrocarbol decreased from the initial 95% to 20%, and the selectivity of 3,4-dihydropyran increased from the initial 98% to the final 99%.

[0082] Comparative Example 7

[0083] MCM-41 catalyst-18# was used to catalyze the dehydration of tetrahydrofurfuryl alcohol to produce 3,4-dihydropyran. The catalysts were pressed into tablets, and the catalysts with a mesh size of 20-40 were sieved and filled into a fixed bed reaction tube with an inner diameter of 6mm and a length of 300mm. The thickness of the catalyst bed was 20mm. Before the reaction, the catalyst was pretreated in flowing nitrogen at 600℃ for 1h. After the pretreatment, the catalyst bed was cooled to a reaction temperature of 200℃, and the mass space velocity of tetrahydrofurfuryl alcohol was 0.5h -1 , under normal pressure. Samples were taken every 2 hours for gas chromatography analysis. After 24 hours of continuous operation, the conversion rate of tetrahydrocarbol decreased from the initial 25% to 3%, and the selectivity of 3,4-dihydropyran decreased from 85% to 70%.

[0084] Comparative Example 8

[0085] MCM-41-based phosphotungstic acid-30 supported catalyst-19# was used to catalyze the dehydration of tetrahydrofurfuryl alcohol to produce 3,4-dihydropyran. The catalysts were pressed into tablets, and the catalysts with a mesh size of 20-40 were sieved and filled into a fixed bed reaction tube with an inner diameter of 6mm and a length of 300mm. The thickness of the catalyst bed was 20mm. Before the reaction, the catalyst was pretreated in flowing nitrogen at 600°C for 1h. After the pretreatment, the catalyst bed was cooled to a reaction temperature of 200°C, and the mass space velocity of tetrahydrofurfuryl alcohol was 0.5h -1 , under normal pressure. Samples were taken every 2 hours for gas chromatography analysis. After 48 hours of continuous operation, the conversion rate of tetrahydrocarbol decreased from the initial 98% to 15%, and the selectivity of 3,4-dihydropyran was maintained at 98%.

Claims

1. A method for preparing 3,4-dihydropyran using mesoporous silicon-based heteropolyacid catalyst, characterized in that: The mesoporous silicon-based heteropoly acid is used as a catalyst to catalyze the dehydration of tetrahydrofurfuryl alcohol to produce 3,4-dihydropyran, and the reaction temperature is 150°C-250°C, preferably 180°C-240°C; The preparation process of the mesoporous silicon-based heteropoly acid catalyst is as follows: under the condition of 20-50° C., concentrated HCl (mass concentration 35-36%) is added to the aqueous solution of the template agent to adjust the pH to 1.2-1.8, ethyl silicate, and heteropoly acid are stirred for 2-48 hours, the obtained colloid is transferred to a hydrothermal kettle, crystallized for 12-72 hours at 50-200° C. (preferably 80-150° C.), filtered, washed, and dried at 80-150° C. for 8-24 hours, and finally calcined at 200-600° C. (preferably 300-500° C.) for 2-12 hours to remove the template agent to obtain a mesoporous silicon-based heteropoly acid catalytic material.

2. A method for preparing 3,4-dihydropyran using mesoporous silicon-based heteropolyacid catalyst, characterized in that: Catalyze the dehydration of tetrahydrofurfuryl alcohol to produce 3,4-dihydropyran, the reaction temperature is 150℃-250℃, preferably 180℃-240℃; The preparation process of the mesoporous silicon-based heteropoly acid catalyst is as follows: sodium hydroxide and silica sol are added to the aqueous solution of the template agent in stoichiometric order, and the molar ratio composition is respectively NaO: template agent is 4:1-1:4, SiO2: template agent is 10:1-1:1, and the mixture is stirred and mixed evenly, and then heteropoly acid is added to obtain an amorphous gel, which is transferred to a hydrothermal reactor and sealed, and crystallized at 50-200° C. (preferably 80-150° C.) for 2-8 days; after the crystallization is completed, the mixture is cooled to room temperature with water, the crystallized product is separated by centrifugation and fully washed with water until it is neutral, and then dried at 80-150° C. for 8-24 hours, and then programmed temperature roasting is performed at 200-600° C. (preferably 250-400° C.) for 6-24 hours (preferably 10-15 hours) to obtain a mesoporous silicon-based heteropoly acid catalytic material.

3. The method according to claim 1 or 2, characterized in that: The active group heteropoly acid of the mesoporous silicon-based heteropoly acid catalyst is one or more of phosphotungstic acid, phosphomolybdic acid, silicotungstic acid, silicomolybdic acid and phosphomolybdic acid.

4. The method according to claim 1, wherein the mass content of the heteropoly acid in the mesoporous silicon-based heteropoly acid catalyst is 2%-60%, preferably 5%-30%.

5. The method according to claim 1 or 2, characterized in that: The mesoporous silica specifically includes one or a mixture of two or more of SBA-15 and SBA-3 in the SBA series and MCM-41, MCM-48 and MCM-50 molecular sieves in the M41S series.

6. The method according to claim 1, 2, characterized in that: The template agent specifically includes one or a mixture of two or more of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), cetyltrimethylammonium bromide (CTAB), cetylpyridinium bromide, polyvinyl alcohol, nonylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, and imidazole long alkyl chain ionic liquid; The imidazolyl long alkyl chain ionic liquid includes [C 14 mim][Br]、[C 16 mim][Br]、[C 18 mim][Br] or a mixture of two or more thereof.

7. The method according to claim 1 or 2, characterized in that: The concentration of the template agent in the aqueous solution is 20-60 mg / mL (preferably 25-40 mg / mL), and the concentration of ethyl silicate in the reaction solution is 50-150 mg / mL (preferably 70-100 mg / mL).

8. The method according to claim 1, characterized in that: The device is a fixed bed reactor, and the reaction is carried out at normal pressure.

9. The method according to claim 8, characterized in that: After the mesoporous silicon-based heteropolyacid-based catalyst is filled in the reaction tube, the reaction tube is placed in a fixed bed reactor for reaction.

10. The method according to claim 8 or 9, characterized in that: The mass space velocity of tetrahydrofurfuryl alcohol feed is 0.1-3.0h -1 , preferably 0.5-2.0h -1 ; The catalyst bed thickness is 10mm-50mm.

Citation Information

Patent Citations

  • Synthetic method of mesoporous and micropore composite molecular sieve catalyst

    CN107497480A

  • Method for preparing tetrahydropyrane by dehydrating and cyclizing 1,5-pentanediol

    CN108148030A

  • Production of 1,5-pentanediol via upgrading of tetrahydrofurfuryl alcohol

    CN108368015A

  • High-stability catalyst for preparing ethylene by dehydrating bioethanol, preparation method and applications thereof

    CN110893348A

  • Production method of 3,4-dihydro-2h-pyran

    JP2017218404A